2020
DOI: 10.7494/geol.2020.46.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Ophiuroids from the Middle Triassic (Muschelkalk) of Sadowa Góra, Jaworzno (southern Poland)

Abstract: Ophiuroids belonging to Aspiduriella sp., Aspiduriella similis (Eck), and Arenorbis sp. are described from the Middle Triassic (Muschelkalk) strata of the Sadowa Góra Quarry (Jaworzno) in southern Poland. This is the only Polish location where three taxa of these ophiuroids have been found in one stratigraphic horizon (1st Wellenkalk). To date, only single taxa have been found in the Triassic sections of the eastern part of the Germanic Basin. Finally, other ophiuroid mass aggregations also known from Poland a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The conducted research confirmed the purposefulness of the revitalization of post‐mining objects in the city of Jaworzno, most often recommending combining many functions, while the protection and access to geological objects revealed during operation and the use of post‐mining objects for recreation and sports has been recommended as the leading direction of transformation (a total of 95.4%). It was found that customer opinions in the form of direct interviews and the results of scientific research carried out in the Sadowa Góra quarry in Jaworzno in the field of geology (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020) may be an effective object management tool. This is evidenced by the high ratings given by the respondents and the steady increase in the number of visitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conducted research confirmed the purposefulness of the revitalization of post‐mining objects in the city of Jaworzno, most often recommending combining many functions, while the protection and access to geological objects revealed during operation and the use of post‐mining objects for recreation and sports has been recommended as the leading direction of transformation (a total of 95.4%). It was found that customer opinions in the form of direct interviews and the results of scientific research carried out in the Sadowa Góra quarry in Jaworzno in the field of geology (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020) may be an effective object management tool. This is evidenced by the high ratings given by the respondents and the steady increase in the number of visitors.…”
Section: Resultsmentioning
confidence: 99%
“…Sadowa Góra (Figure 1) quarry is an rea of a lower rank but can be seen as a good example of a space effectively used for public benefit, combining all the most important features of non‐reclaimed post‐mining sites, landscape and educational: fossil remains of vertebrates, echinoderms, brachiopods, etc. (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020). The quarry is a highly valued tourist attraction because of its scenic qualities, as well as its technical infrastructure elements representing historical value and development elements defining the quality of conditions for use of the facility by end‐users.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation